Online Classes Amid The Covid-19 Pandemic: Parents Perspective - Khan, Dr. Sohail Imran . (The journal of contemporary issues in business and government, 2021)
Online learning and online classes have been widely elevated to replace customary face to face methods of learning during this Covid-19 pandemic to keep up small kids learning and play at home. This research works overviewed 183 Indian parents’ attitude and perception for young children’s online learning during the lockdown of the Covid-19 pandemic. 10 different schools were selected for the study. Survey method was used to collect primary data. SPSS (version 24) was used to convert this primary data into information so as to draw a conclusion. With an objective to understand the parent’s perception and opinion about online classes, it was concluded that parents are very well adjusted and satisfy about this methodology of learning. They opined that online learning has a positive influence on learning on the children and it is the need of the hour during this pandemic.